Utilization of Oral Hyperglycemic Drugs Among Type 2 Diabetes Patients in Indonesia’s Major Maize-Producing Region - Nasrun Pakaya; Hartono Hadjarati; Gusti Pandi Liputo (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Diabetes Mellitus (Diabetes) is a degenerative and chronic disease caused by impaired carbohydrate metabolism due to insulin hormone insufficiency. Data from the Gorontalo Provincial Health Department in 2023 showed that there were 18.299 cases of diabetes mellitus diagnosed. The study aimed to analyze the use of oral hyperglycemic drugs in patients with type 2 diabetes mellitus in Bone Bolango Regency, Gorontalo Province. This research is a quantitative study with an observational analytical approach using a cross-sectional design. The population of this study was diabetic patients who were using oral hyperglycemic drugs in the Kabila Health Center area, with 126 people selected using the total sampling method. The data on gender, age, income, health worker support, and family support were analyzed using binary logistic regression. The results showed a significant difference between income (P = 0.013) and health worker support (P = 0.022) with compliance. In contrast, the gender (P = 0.333) and family support (P = 0.070) did not significantly differ in compliance. Each category that had significant differences was subjected to multivariate analysis. The results showed no difference in compliance based on gender (P = 0.235), 2). However, there was a difference in compliance based on age (P = 0.022) and income level (P = 0.020). The variable explaining the dependent variable was only 19.5%, and the rest was described by other variables outside the research model (80.5%). The statistical analysis concluded that 1) gender variables (Sig 0.333) and family support (0.070) did not have a significant effect on compliance, 2) income variables (0.013) and health worker support (0.022) had a significant effect on compliance.